mVOC 4.0: a database of microbial volatiles - Emanuel Kemmler; Marie Chantal Lemfack; Andrean Goede; Kathleen A. Gallo; Serge M T Toguem; Waqar Ahmed; Iris Millberg; Saskia Preißner; Birgit Piechulla; Robert Preißner (2024)
Abstract Metabolomic microbiome research has become an important topic for understanding agricultural, ecological as well as health correlations. Only the determination of both the non-volatile and the volatile organic compound (mVOC) production by microorganisms allows a holistic view for understanding the complete potential of metabolomes and metabolic capabilities of bacteria. In the recent past, more and more bacterial headspaces and culture media were analyzed, leading to an accumulation of about 3500 mVOCs in the updated mVOC 4.0 database, including compounds synthesized by the newly discovered non-canonical terpene pathway. Approximately 10% of all mVOCs can be assigned with a biological function, some mVOCs have the potential to impact agriculture in the future (e.g. eco-friendly pesticides) or animal and human health care. mVOC 4.0 offers various options for exploring extensively annotated mVOC data from different perspectives, including improved mass spectrometry matching. The mVOC 4.0 database includes literature searches with additional relevant keywords, making it the most up-to-date and comprehensive publicly available mVOC platform at: http://bioinformatics.charite.de/mvoc.